IL‐17 polarization of MAIT cells is derived from the activation of two different pathways. Issue 11 (8th November 2017) - Guggino, Giuliana; Di Liberto, Diana; Lo Pizzo, Marianna; Saieva, Laura; Alessandro, Riccardo; Dieli, Francesco; Triolo, Giovanni; Ciccia, Francesco
Abstract : MAIT cells are expanded in salivary glands of patients with Sjogren's syndrome and are IL‐17 polarized. IL‐7 and IL‐23 induce IL‐17 production activating two different pathways: IL‐7 stimulation induces in fact a significant STAT3 and HIF1alpha upregulation, conversely, IL‐23 stimulation significantly induces RORc overexpression in MAIT cells of patients with Sjogren's syndrome.